Cellulase and Xylanase Production from Rice Straw by a Locally Isolated Fungus Aspergillus fumigatus NITDGPKA3 under Solid State Fermentation – Statistical Optimization by Response Surface Methodology - Sarkar, Nibedita; Aikat, Kaustav (Journal of Technology Innovations in Renewable Energy, 2012)
Alkali pretreated rice straw was used as substrate for cellulase production by a locally isolated fungus Aspergillus fumigatus NITDGPKA3 under solid state fermentation. Critical process parameters such as incubation period, temperature, basal medium content and pH were statistically optimized for an enhanced cellulase and xylanase yield by response surface methodology. The design predicted an optimum yield of 3.1 IU/g dry substrate, 64.18 IU/g dry substrate and 1040.57 IU/g dry substrate for FPase, CMCase and xylanase respectively under the optimum conditions of incubation period of 90 h, temperature at 33oC, initial basal medium content of 62% and initial pH 4. The experimental values under optimum conditions correlated well with the predicted results. Further, crude enzyme extract from Aspergillus fumigatus NITDGPKA3 was used for saccharification of pretreated rice straw and this released 189.50 mg/g of reducing sugar. This work was carried out in the Department of Biotechnology, National Institute of Technology, Durgapur-713209, West Bengal, India, during the period 2010 to 2011.